2008
DOI: 10.1080/09546630701759587
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy of adalimumab in generalized pustular psoriasis

Abstract: In this case, adalimumab has been demonstrated to be effective, safe and appropriate for long-term use, indicating a beneficial effect on quality of life parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 17 publications
1
30
1
Order By: Relevance
“…The PASI scores were stably maintained over 48 weeks, even following a reduction to weekly 50 mg dosing at 24 weeks. Adalimumab has shown efficacy in adolescence and adulthood through 72 weeks of treatment (grade D evidence) [8082]. …”
Section: Resultsmentioning
confidence: 99%
“…The PASI scores were stably maintained over 48 weeks, even following a reduction to weekly 50 mg dosing at 24 weeks. Adalimumab has shown efficacy in adolescence and adulthood through 72 weeks of treatment (grade D evidence) [8082]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that this paradoxical response appears to involve a disruption in cytokine balance following TNFα inhibition, resulting in the upregulation of plasmacytoid dendritic cells and the subsequent production of unopposed interferon-alpha, following a triggering event in predisposed individuals 102. Notably, adalimumab has not only been reported to cause pustular psoriasis, but also to be effective in the treatment of recalcitrant generalized pustular psoriasis in adults and adolescents 83,84…”
Section: Resultsmentioning
confidence: 99%
“…Multiple reports on the induction or exacerbation of psoriasis in patients treated with TNF-α antagonists exist,51 including such cases associated with adalimumab as new onset generalized pustular psoriasis and52 pustular psoriasis of the scalp 51. Although it has been reported to cause pustular psoriasis, adalimumab has also been found to be effective in the treatment of recalcitrant generalized pustular psoriasis in adults53 and adolescents 54. Therefore, adalimumab-induced psoriasis requires discontinuation of adalimumab only in cases unresponsive to topical anti-psoriatic treatment.…”
Section: Safety and Tolerability Of Adalimumab In The Long-term Treatmentioning
confidence: 99%